A field investigation into the impact of task demands on worker responses in the South African forestry silviculture sector - Parker, Rhiannon Jennifer (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2014)
Background: In South Africa, limited research has focused on the task demands and workers responses associated with forestry silviculture work, particularly pitting and planting. The methods currently in use are manual, but despite our lack of understanding of the existing demands, advances in forestry engineering have resulted in an introduction of semi-mechanised versions of these tasks. This project aimed to compare the task demands of silviculture tasks using the current manual techniques and the more modern, semi-mechanised techniques. Methods: A holistic investigation focused on the worker characteristics of a sample of black male pitters and black female planters from the Kwa-Zulu Natal forestry industry, as well as biomechanical (spinal kinematics and L5/S1 forces), physiological (heart rate, oxygen consumption and energy expenditure) and psychophysical (ratings of perceived exertion and body discomfort) responses associated with manual and semi-mechanised pitting and planting. Results: The pitting task saw significant improvements in the spinal kinematic measures as a result of the increased mechanisation, with eight of the 16 recorded variables decreasing to a lower level of risk classification. Physiologically, the manual task was associated with a mean heart rate of 157 bt.minâ »Â¹ and absolute energy expenditure of 11.27 kcal.minâ »Â¹, which were not found to be significantly different to the values of 143 bt.minâ »Â¹ and 9.8 kcal.minâ »Â¹ recorded during the semi-mechanised technique. Psychophysical responses indicated that the workers perceived manual pitting to be more physically demanding than the semi-mechanised method. The manual and semi-mechanised planting tasks were, in general, found to be acceptable from a spinal kinematics perspective, with the majority of variables classified as low risk. However, the maximum sagittal angle was reduced by more than 20 degrees as a result of the new equipment. The physiological and psychophysical demands associated with manual planting were found to be within acceptable limits. Conclusion: In terms of pitting, it can tentatively be concluded that the semi-mechanised technique is better than the manual one, based on the biomechanical and psychophysical findings, however physiological demands require further investigation. When considering the planting techniques, the semi-mechanised method showed a slight improvement from the biomechanical perspective, but further physiological and psychophysical investigations are needed.
Keywords: Forests and forestry -- South Africa -- KwaZulu-Natal; Blue collar workers -- South Africa -- KwaZulu-Natal; Manual work -- South Africa -- KwaZulu-Natal; Work -- Physiological aspects; Human mechanics